Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd008856
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce corruption in the health sector

Abstract: Background Corruption is the abuse or complicity in abuse, of public or private position, power or authority to benefit oneself, a group, an organisation or others close to oneself; where the benefits may be financial, material or non-material. It is widespread in the health sector and represents a major problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 8 publications
0
47
0
6
Order By: Relevance
“…Some reviews focused on specific accountability interventions, such as health committees ( McCoy et al , 2012 ; George et al , 2015b ), social audits ( Pattinson et al , 2009 ) and report cards ( McNamara, 2006 ; Gullo et al , 2016 ). Others looked at systems-level change through decentralization ( Talukder et al , 2008 ; Mitchell and Bossert, 2010 ; Cobos Muñoz et al , 2017 ) or efforts to reduce corruption ( Vian, 2008 ; Hanna et al , 2011 ; Ciccone et al , 2014 ; Gaitonde et al , 2016 ; Molina et al , 2016 ). Most reviews sought to identify interventions that influence accountability and thus discussed a range of interrelated interventions and outcomes ranging from health system responsiveness to maternal mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reviews focused on specific accountability interventions, such as health committees ( McCoy et al , 2012 ; George et al , 2015b ), social audits ( Pattinson et al , 2009 ) and report cards ( McNamara, 2006 ; Gullo et al , 2016 ). Others looked at systems-level change through decentralization ( Talukder et al , 2008 ; Mitchell and Bossert, 2010 ; Cobos Muñoz et al , 2017 ) or efforts to reduce corruption ( Vian, 2008 ; Hanna et al , 2011 ; Ciccone et al , 2014 ; Gaitonde et al , 2016 ; Molina et al , 2016 ). Most reviews sought to identify interventions that influence accountability and thus discussed a range of interrelated interventions and outcomes ranging from health system responsiveness to maternal mortality.…”
Section: Resultsmentioning
confidence: 99%
“…How can we better analyse the dynamics of social accountability strategies? Gaitonde et al (2016) Systematic review Global Corruption What strategies have been used and how effective are they to reduce corruption in the health sector? Gaventa and Barrett (2010) Qualitative synthesis (meta-case study analysis) LMIC Outcomes of citizen engagement What is the impact of participation on improved democratic and developmental outcomes?…”
Section: Resultsmentioning
confidence: 99%
“…Other reviews stated that browsing was conducted without providing more detail and/or reported search terms. [50][51][52][53] Of the 3 reviews that reported the number of results identified by searching websites, 2 reported the total number of results 25,49 and 1 reported that a website was searched for information about an ongoing study. 54 A total of 25 searches were reported with a median of 30 results (range 0-892).…”
Section: Additional Details Reported About Websitesmentioning
confidence: 99%
“…Their involvement in a collective drive to demonstrate success can unintentionally ‘instil a fear of failure, stifle risk-taking and innovation, and lead to the fabrication of achievement’ 9. For example, research that threatens the position of powerful elites—such as research into high-level corruption—is lacking 10. Meanwhile, selective reporting of ‘unwelcome’ findings can be a way to avoid contractual terminations even though it undermines learning 1 11 12.…”
Section: Introductionmentioning
confidence: 99%